Raising patient voices in medical education: an assessment of patient perceived effect of social determinants of health conversations and the patient-physician relationship on quality of obstetric care, to inform the development of patient driven medical education curricula - Brito, S.; Rau, A.; Escobar, C.; Garza, P.; Sriprasert, I.; Mitchell Chadwick, N. (Frontiers in Reproductive Health, 2024)
Background: Conventional medical education lacks the lived experiences of patients which may authentically convey the social determinants of health (SDOH) and resulting health disparities. Videos of first-person patient narratives may prove a valuable education tool in this regard. The objective of this study is to investigate how patient demographics, satisfaction with care, and patient-physician relationships influence obstetric patient interest and willingness to contribute to SDOH video by sharing their lived experiences through first-person narratives. Methods: Study design included an anonymous, cross-sectional survey and an optional semi-structured telephone interview. Participants were +18 years old with a live-birth delivery < 8 weeks prior to recruitment and received care during their pregnancy at Los Angeles General Medical Center (LAGMC). Variables surveyed included demographics, satisfaction with care, aspects of the patient-physician relationship, perceived utility, and personal interest in contributing to an educational SDOH video. A bivariate analysis was conducted to compare participants' characteristics and responses on interest in contributing and perceived helpfulness of first-person patient SDOH video. Results: Of the (N = 70) 72.43% of participants believed a patient’s first-person video on SDOH would be “Helpful” in preparing physicians to provide competent medical care; however, 71.43% responded “No'' to “Interest” in sharing their experiences with SDOH with physicians. English preference and being U.S. born were factors significantly associated with viewing first-person SDOH video as “Helpful” (P > 0.001). Major themes from telephone interviews reflected enthusiasm for first-person patient narratives and perceived benefits of using patient experiences to educate physicians on SDOH. However, participants cited barriers to disclosing SDOH including brief and strictly clinical interactions with physicians, lack of continuity of care, and fear of being judged by physicians. Conclusion: While most participants recognized the utility of addressing social needs in medical education and reported satisfaction with their obstetricians and care, these factors did not uniformly translate into willingness to contribute first-person patient narratives. To improve representation of patients from racial, ethnic, gender, linguistic, and sexual minorities into medical curricula, further research and strategies are needed to overcome the barriers to patient involvement.